Compact 2025: Ending hunger and undernutrition 2015 - Compact 2025 (International Food Policy Research Institute, 2015)
Hunger and undernutrition are two of the greatest scourges facing our planet today. We can eliminate both, and we can do so by 2025—which will also help end extreme poverty and will contribute to achieving multiple Sustainable Development Goals. But there are significant knowledge gaps related to eliminating hunger and undernutrition that must first be filled for effective and cost-efficient action. Compact2025 will address these gaps by acting as a Knowledge and Innovation Hub that will help guide countries in developing and implementing strategic actions for food security and nutrition. By working across sectors and with multiple stakeholders to provide evidence-based knowledge with an emphasis on country-led progress, Compact2025 will contribute to the achievement of global food security and nutrition by 2025.